Separation of rare earths from transition metals by liquid-liquid extraction from a molten salt hydrate to an ionic liquid phase - Rout, Alok; Binnemans, Koen (Dalton transactions : an international journal of inorganic chemistry, 2014)
The solvent extraction of trivalent rare-earth ions and their separation from divalent transition metal ions using molten salt hydrates as the feed phase and an undiluted fluorine-free ionic liquid as the extracting phase were investigated in detail. The extractant was tricaprylmethylammonium nitrate, [A336][NO3], and the hydrated melt was calcium nitrate tetrahydrate, Ca(NO3)2·4H2O. The extraction behavior of rare-earth ions was studied for solutions of individual elements, as well as for mixtures of rare earths in the hydrated melt. The influence of different extraction parameters was investigated: the initial metal loading in the feed phase, percentage of water in the feed solution, equilibration time, and the type of hydrated melt. The extraction of rare earths from Ca(NO3)2·4H2O was compared with extraction from CaCl2·4H2O by [A336][Cl] (Aliquat 336). The nitrate system was found to be the better one. The extraction and separation of rare earths from the transition metals nickel, cobalt and zinc were also investigated. Remarkably high separation factors of rare-earth ions over transition metal ions were observed for extraction from Ca(NO3)2·4H2O by the [A336][NO3] extracting phase. Furthermore, rare-earth ions could be separated efficiently from transition metal ions, even in melts with very high concentrations of transition metal ions. Rare-earth oxides could be directly dissolved in the Ca(NO3)2·4H2O phase in the presence of small amounts of Al(NO3)3·9H2O or concentrated nitric acid. The efficiency of extraction after dissolving the rare-earth oxides in the hydrated nitrate melt was identical to extraction from solutions with rare-earth nitrates dissolved in the molten phase. The stripping of the rare-earth ions from the loaded ionic liquid phase and the reuse of the recycled ionic liquid were also investigated in detail.